Desorption electrospray ionization mass spectrometry imaging in discovery and development of novel therapies. Issue 2 (13th October 2021) - Soudah, Terese; Zoabi, Amani; Margulis, Katherine
Abstract: Desorption electrospray ionization mass spectrometry imaging (DESI‐MSI) is one of the least specimen destructive ambient ionization mass spectrometry tissue imaging methods. It enables rapid simultaneous mapping, measurement, and identification of hundreds of molecules from an unmodified tissue sample. Over the years, since its first introduction as an imaging technique in 2005, DESI‐MSI has been extensively developed as a tool for separating tissue regions of various histopathologic classes for diagnostic applications. Recently, DESI‐MSI has also emerged as a versatile technique that enables drug discovery and can guide the efficient development of drug delivery systems. For example, it has been increasingly employed for uncovering unique patterns of in vivo drug distribution, the discovery of potentially treatable biochemical pathways, revealing novel druggable targets, predicting therapeutic sensitivity of diseased tissues, and identifying early tissue response to pharmacological treatment. These and other recent advances in implementing DESI‐MSI as the tool for the development of novel therapies are highlighted in this review. Abstract :